Imperial temporalities, insurgent futures comparisons of 20th century political thinkers in Indonesia and the Philippines - Magaling, Christian Lemuel M.
This research attempts to link and rethink the synchronicity of ideas by contemporary political thinkers in Southeast Asia, through an empirical analysis of the discourses deployed in the principal writings of pre-independence thinkers from Indonesia and the Philippines. This research uses methods in digital humanities to enable a network analysis using close(r) reading (Guillermo, 2018) by operating on a combination of concordance and collocational analysis to selected political pamphlets together with their translations to aid in conceptualizing the co-presence of revolutions. In rethinking the "contemporary" social movements that gather around in addressing the shift from colonial to imperial temporality in Southeast Asia as an area of study, these comparisons enable an aspect of decolonizing the approach to intellectual dialogues between Europe and Southeast Asia within the historical temporality of 20th century imperialism.